Representation Of Women In Parliament Of Bangladesh: Is It Hopeful? - Jannatul Ferdous (Journal of Governance and Public Policy, 2019)
The poor representation of women in nearly each policy-making facet of life is a universal matter. In the entire world, women are represented in government in poor ratio to their entire populace. A component of representative democracy is that irrespective of gender, all people have equal prospects to partake in the political arena. In elective points, better representation of women of power is a matter of fairness and parity. Yet, representation of women in many parliaments is often limited. Democracy cannot embellish without a rational representation of women in the parliament, which is the most influential organization of democratic states. The analytical structure of this study undertakes that the presence of women in parliament does not inevitably turn into the functional picture rather it is a result of organizational, sociological and institutional facets. This has failed to make an effective impact on the representation of women in Parliament in a particular political situation. Therefore, the issues that impede or enable women’s representation in elective points differ with the issue of socioeconomic progress, culture and the form of political arrangement. The author has taken a modest endeavor to disclose about the significant matters linked to women’s poor representation in Bangladesh Parliament.